Resource Scarcity, Spite and Cooperation - Prediger, Sebastian; Vollan, Björn; Herrmann, Benedikt (IDEAS Working Paper Series from RePEc, 2013)
Using an experimental approach, this paper examines how scarcity of natural resources affects people's readiness to cooperate or engage in antisocial behavior. The experiments were carried out with pastoralists from southern Namibia, whose livelihoods greatly depend on grazing availability on collectively used rangelands. We split the study region into two areas according to exogenous differences in biomass production (a high-yield and a low-yield area) and conducted a one-shot public goods experiment and a joy-of-destruction experiment with pastoralists from both areas. Results from the joy-of-destruction experiment reveal that a substantial proportion of people are willing to reduce another subject's income, although this comes at a personal cost. We show that this kind of spiteful behavior occurs twice as often in the area where resources are scarcer and hence competitive pressure is higher. By contrast, levels of cooperation are very similar across areas. This indicates that scarcity does not hamper cooperation, at least as long as a subsurvival level has not been exceeded. Our data further reveal a coexistence of prosocial and antisocial behavior within individuals, suggesting that people's motivations depend on the experimental environment they are acting in. One possible explanation is that subjects are ready to cooperate when substantial net gains can be realized, but turn into spiteful money burners when there is no scope for efficiency improvements and the risk of falling behind is particularly salient.